Clinical and trichoscopic features in various forms of scalp psoriasis. (7th June 2021) - Bruni, F.; Alessandrini, A.; Starace, M.; Orlando, G.; Piraccini, B.M.
Abstract: Background: Scalp psoriasis is often undiagnosed or inadequately treated. The patient himself underestimates the seriousness of this hair disease and consults too late to a dermatologist. Objectives: The aim of our study was to create a correlation between the clinical patterns and trichoscopy of scalp psoriasis such in a way to help the clinician to make the diagnosis and select the appropriate therapy. Material and methods: We gathered all patients affected of scalp psoriasis afferent to Outpatient's hair consultation of the Department of Experimental, Diagnostic and Specialty Medicine, University of Bologna, from January 2012 to December 2018. All patients were evaluated through clinical, trichoscopic examination and a skin biopsy only in doubtful cases. We quantified the severity of the disease with several objective and subjective parameters every 4 months, up to 1 year. We recorded therapies, outcome data and quality of life. Results: We collected 156 patients affected by scalp psoriasis, identifying seven clinical patterns with specific trichoscopical correlation. In the order of frequency, the clinical patterns were as follows: plaque psoriasis (with a prevalence of erythema, silver‐white scales and twisted red loops vessels and red dots); thin scales (with silvery‐white scales, simple red lines and signet red ring vessels); sebopsoriasis (with greasy scales, erythema with red dots, globules and twisted and bushy red loops at high magnification); psoriatic cap (with silver‐white scales, erythema and polymorphic vascular pattern); pityriasis amiantacea (with yellowish adherent scales, erythema and simple red loops capillaries); cicatricial psoriatic alopecia (with erythema associated with yellowish, silver‐white scales with twisted and bushy red loops capillaries) and pustular psoriasis (with 'flower shape' pustular lesions, erythema simple red loops capillaries). Conclusions: The description of different clinical patterns of scalp psoriasis and its trichoscopical correlations may help the clinician to make the diagnosis also in atypical presentations and to prescribe an adequate therapeutic regimen. Abstract : Linked Commentary: F. Lacarrubba. J Eur Acad Dermatol Venereol 2021; 35 : 1744–1745. https://doi.org/10.1111/jdv.17527 .